Dynamic alterations of bone marrow cytokine landscape of myelodysplastic syndromes patients treated with 5-azacytidine - Moudra, Alena; Hubackova, Sona; Machalova, Veronika; Vancurova, Marketa; Bartek, Jiri; Reinis, Milan; Hodny, Zdenek; Jonasova, Anna (Oncoimmunology, 2016)
Myelodysplastic syndromes (MDS) represent a heterogeneous group of clonal stem cell disorders characterized by ineffective hematopoiesis frequently progressing into acute myeloid leukemia (AML), with emerging evidence implicating aberrant bone marrow (BM) microenvironment and inflammation-related changes. 5-azacytidine (5-AC) represents standard MDS treatment. Besides inhibiting DNA/RNA methylation, 5-AC has been shown to induce DNA damage and apoptosis in vitro. To provide insights into in vivo effects, we assessed the proinflammatory cytokines alterations during MDS progression, cytokine changes after 5-AC, and contribution of inflammatory comorbidities to the cytokine changes in MDS patients. We found that IL8, IP10/CXCL10, MCP1/CCL2 and IL27 were significantly elevated and IL12p70 decreased in BM of MDS low-risk, high-risk and AML patients compared to healthy donors. Repeated sampling of the high-risk MDS patients undergoing 5-AC therapy revealed that the levels of IL8, IL27 and MCP1 in BM plasma were progressively increasing in agreement with in vitro experiments using several cancer cell lines. Moreover, the presence of inflammatory diseases correlated with higher levels of IL8 and MCP1 in low-risk but not in high-risk MDS. Overall, all forms of MDS feature a deregulated proinflammatory cytokine landscape in the BM and such alterations are further augmented by therapy of MDS patients with 5-AC.
Keywords: inflammation; myelodysplastic syndromes; 5-azacytidine; cytokines; DNA damage; bone marrow plasma